Indoor Localization And Direction Sensing Via RFID Approach - Ruzaidi, Nurul Effah (Universiti Sains Malaysia, 2018)
Radio Frequency Identification is a kind of device that use radio frequency to communicate. RFID application has been widely used in indoor localization system. An efficient indoor localization system is needed to find the unknown location of an object. The main purpose of this project is to reduce the error of estimated distance from transmitter and receiver. This system using RFID technology to make the system is more effective. The main hardware used in this project is Xbee module. Xbee module can be set to work as RFID system by using XCTU software which is coordinator as reader and end device or router work as tag. Method apply in this project is RSSI which is to measure the signal between transmitter and receiver. From the RSSI value, estimated distance can be calculated by using equation. Next, trilateration is used to locate the position of the unknown node. To apply trilateration method, distance value needed is at least for three point. From the distance value, a circle will be formed for each distance as their radius. The result of simulation of Matlab will display the screen with the three circles. The intersection of three circle is where the unknown node is. The accuracy of location from trilateration result is able to be reduced about 4.39% for this system compared to the previous work.